Mexico - Fiscal Sustainability (Vol. 1 of 2) : Executive Summary - World Bank (Washington, DC, 2013)
The study reviews the stabilization efforts, and successes that preceded, and have underpinned Mexico's sweeping market-oriented structural reforms since the late 1980s, anchored in strong fiscal adjustment. It seeks to support the Government's efforts, and provides a body of technical analysis, by: correcting fiscal trends for various business-cycle effects; building a simulation model to assess the sensitivity of the fiscal budget to exogenous shocks under structural scenarios; estimating the direct, and indirect potential impact on the fiscal accounts of closing public infrastructure gaps, and funding contingent liabilities; and, consolidating the financial accounts of the main public sector institutions to assess sustainability of their aggregate debt path. Following a brief review on fiscal issues, the report focuses on selected sources of fiscal instability. Chapter I questions the role of fiscal policy in determining output; the responsiveness of the fiscal policy to the business cycle; and, the "persistence" of fiscal policy vs. financing needs, implying the fiscal policy lacks a design that makes it a stabilizing feature of the economy. Chapters II and III investigate the impacts of major exogenous shocks, and provide estimates of the potential payoffs from increased investment in public infrastructure, calculating the optimal infrastructure stocks implied by the elasticity estimates. Chapter IV addresses the measurement of contingent liabilities, within the traditional budget accounting framework, while Chapter V provides estimates of the debt stock at the state level, suggesting disturbing trends in the size, and concentration of the debt are developing, and, sobering evidence on the health of the sub-national pension systems suggest a large percentage of these are either in actuarial deficit, or will be by 2001.